Blood Glutamate Levels in Autism Spectrum Disorder: A Systematic Review and Meta-Analysis. - Zhen Zheng; Tingting Zhu; Yi Qu; Dezhi Mu (PLoS ONE)
Objective Glutamate plays an important role in brain development, neuronal migration, differentiation, survival and synaptogenesis. Recent studies have explored the relationship between blood glutamate levels and autism spectrum disorder (ASD). However, the findings are inconsistent. We undertook the first systematic review with a meta-analysis of studies examining blood glutamate levels in ASD compared with controls. Methods A literature search was conducted using PubMed, Embase, and the Cochrane Library for studies published before March 2016. A random-effects model was used to calculate the pooled standardized mean difference (SMD) of the outcomes. Subgroup analyses were used to explore the potential sources of heterogeneity, and the publication bias was estimated using Egger's tests. Results Twelve studies involving 880 participants and 446 incident cases were included in this meta-analysis. The meta-analysis provided evidence for higher blood glutamate levels in ASD [SMD = 0.99, 95% confidence interval (95% CI) = 0.58-1.40; P < 0.001] with high heterogeneity (I2 = 86%, P < 0.001) across studies. The subgroup analyses revealed higher glutamate levels in ASD compared with controls in plasma [SMD = 1.04, 95% CI = 0.58-1.50; P < 0.001] but not true in serum [SMD = 0.79, 95% CI = -0.41-1.99; P = 0.20]. Studies employing high performance liquid chromatography (HPLC) or liquid chromatography-tandem mass spectrometry (LC-MS) assays also revealed higher blood glutamate levels in ASD. A sensitivity analysis found that the results were stable, and there was no evidence of publication bias. Conclusions Blood glutamate levels might be a potential biomarker of ASD.